Natural variation of life‐history traits, water use, and drought responses in Arabidopsis. (1st February 2018) - Ferguson, John N.; Humphry, Matt; Lawson, Tracy; Brendel, Oliver; Bechtold, Ulrike
Abstract: The ability of plants to acquire and use water is critical in determining life‐history traits such as growth, flowering, and allocation of biomass into reproduction. In this context, a combination of functionally linked traits is essential for plants to respond to environmental changes in a coordinated fashion to maximize resource use efficiency. We analyzed different water‐use traits in Arabidopsis ecotypes to identify functionally linked traits that determine water use and plant growth performance. Water‐use traits measured were (i) leaf‐level water‐use efficiency (WUE i ) to evaluate the amount of CO2 fixed relative to water loss per leaf area and (ii) short‐term plant water use at the vegetative stage (VWU) as a measure of whole‐plant transpiration. Previously observed phenotypic variance in VWU, WUE i and life‐history parameters, highlighted C24 as a valuable ecotype that combined drought tolerance, preferential reproductive biomass allocation, high WUE i, and reduced water use. We therefore screened 35 Arabidopsis ecotypes for these parameters, in order to assess whether the phenotypic combinations observed in C24 existed more widely within Arabidopsis ecotypes. All parameters were measured on a short dehydration cycle. A segmented regression analysis was carried out to evaluate the plasticity of the drought response and identified the breakpoint as a reliable measure of drought sensitivity. VWU was largely dependent on rosette area, but importantly the drought sensitivity and plasticity measures were independent of the transpiring leaf surface. A breakpoint at high rSWC indicated a more drought‐sensitive plant that closed stomata early during the dehydration cycle and consequently showed stronger plasticity in leaf‐level WUE i parameters. None of the sensitivity, plasticity, or water‐use measurements were able to predict the overall growth performance; however, there was a general trade‐off between vegetative and reproductive biomass. PCA and hierarchical clustering revealed that C24 was unique among the 35 ecotypes in uniting all the beneficial water use and stress tolerance traits, while also maintaining above average plant growth. We propose that a short dehydration cycle, measuring drought sensitivity and VWU is a fast and reliable screen for plant water use and drought response strategies.